Variable spatiotemporal resolution three‐dimensional dixon sequence for rapid dynamic contrast‐enhanced breast MRI. Issue 6 (December 2014) - Saranathan, Manojkumar; Rettmann, Dan W.; Hargreaves, Brian A.; Lipson, Jafi A.; Daniel, Bruce L.
<x xml:space="preserve">Abstract</x> Purpose To investigate a new variable spatiotemporal resolution dynamic contrast‐enhanced (DCE) MRI method termed DIfferential Subsampling with Cartesian Ordering (DISCO), for imaging of breast cancer. Materials and Methods DISCO combines variable density, pseudorandom k‐space segmentation and two‐point Dixon fat–water separation for high spatiotemporal resolution breast DCE MRI. During the contrast wash‐in phase, view sharing is used to achieve high temporal resolution. Forty patients referred for breast MRI were imaged, 26 using the proposed DISCO sequence and 14 using a conventional low‐spatial‐resolution dynamic sequence (VIBRANT‐FLEX) on a 3 Tesla scanner. DISCO dynamic images from 14 patients were compared with VIBRANT‐FLEX images from 14 other patients. The image quality assessed by radiologist image ranking in a blinded manner, and the temporal characteristics of the two sequences were compared. Results A spatial resolution of 1.1 × 1.1 × 1.2 mm3 (160 slices, 28 cm field of view) was achieved with axial bilateral coverage in 120 s. Dynamic images with ∼9 s effective temporal resolution were generated during the 2‐min contrast wash‐in phase. The image quality of DISCO dynamic images ranked significantly higher than low spatial resolution VIBRANT‐FLEX images (19.5 versus 9.5, Mann‐Whitney U‐test P = 0.00914), with no significant differences in the maximum slope of aortic enhancement. Conclusion DISCO is a promising variable‐spatiotemporal‐resolution imaging sequence for capturing the dynamics of rapidly enhancing tumors as well as structural features postcontrast. A near 1‐mm isotropic spatial resolution was achieved with postcontrast static phase images in 120 s and dynamic phase images acquired in 9 s per phase. J. Magn. Reson. Imaging 2014;40:1392–1399. © 2013 Wiley Periodicals, Inc.